Price discovery in spot and futures markets: A reconsideration - Erik Theissen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
We reconsider the issue of price discovery in spot and futures markets. We use a threshold error correction model to allow for arbitrage operations to have an impact on the return dynamics. We estimate the model using quote midpoints, and we modify the model to account for time-varying transaction costs. We find that the futures market leads in the process of price discovery. The lead of the futures market is more pronounced in the presence of arbitrage signals. Thus, when the deviation between the spot and the futures market is large, the spot market tends to adjust to the futures market.
urn:nbn:de:hebis:30-73571
Keywords: G13; G14; 330; Futures Markets; Threshold Error Correction; Information Shares; Common Factor Weights; Spotmarkt; Termingeschäft; Elektronisches Handelssystem; Preis; Mikrostrukturanalyse; Fehlerkorrekturmodell